Pelatihan Diversifikasi Olahan Susu Sapi Untuk Kemandirian Ekonomi Perempuan Peternak Kepuharjo Cangkringan - Dyah Wahyuning Tyas; Maya Dewi Savitri; Farah Diana Djamil; Danang Prasetyo (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity was driven by the need to increase the added value of raw cow’s milk and empower the economic participation of female dairy farmers in Kepuharjo Village, Cangkringan District, Sleman Regency, Yogyakarta. Historically, fresh milk produced by local farmers was predominantly sold raw at low market prices, while the involvement of farmers' wives in productive economic activities within the Merapi tourism area remained underutilized. This program aimed to enhance the technical knowledge and skills of community partners in processing raw milk into high-value, ready-to-consume products. A participatory qualitative approach was employed, incorporating interactive workshops, practical demonstrations, and skill observation evaluations. The intervention focused on processing fruit-flavored milk, as well as milk pies, integrated with basic home-based food hygiene practices. The results revealed a significant increase in participants' technical competencies, achieving an overall average score of 88,25% (Highly Skilled category). The highest achievements were recorded in product organoleptic quality (93.0%) and packaging and labeling (89.0%). This product diversification not only yielded market-ready products suitable for local tourists but also successfully strengthened women's strategic economic roles, fostering sustainable household financial independence.